-5m+13=-27

Simple and best practice solution for -5m+13=-27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5m+13=-27 equation:


Simplifying
-5m + 13 = -27

Reorder the terms:
13 + -5m = -27

Solving
13 + -5m = -27

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-13' to each side of the equation.
13 + -13 + -5m = -27 + -13

Combine like terms: 13 + -13 = 0
0 + -5m = -27 + -13
-5m = -27 + -13

Combine like terms: -27 + -13 = -40
-5m = -40

Divide each side by '-5'.
m = 8

Simplifying
m = 8

See similar equations:

| x=2(x+16) | | x-18/x=-3 | | x/7=70 | | 1000=55000+7X | | 6+2.135=3.51n | | 7-2q/5=q | | 6+2.135=3.15n | | 1/x=5/12 | | 1/x=1/2 | | -13x+5x=15 | | 1/x=-9/35 | | 1/x=-1/8 | | x/3=17/14 | | 2/3x-5=5/3x | | 7—2q/5=q | | 6x+2(6x-6)=8x-7 | | 5/9x-4=21 | | X-17/6=7/12 | | 12+(7+m)=30 | | 0.5m+0.2n=5 | | 8-3x+9+2x+2x-5=5+3*4 | | 10x-6x+3x=-42 | | 0.6m+0.4n=8.4 | | Y=3g(x+2)+1 | | 8-6x+11+3x+4x-5=8+3*4 | | Y=3g(x+2)-1 | | 25y^4/10y^9 | | 40=28-5c | | Y1/4x-2 | | ln(x^2-3)=3.2 | | 0.10t+0.11(t+400)=212 | | -5x+10x-4x=15-36 |

Equations solver categories